Capabilities of percutaneous biopsy methods to preoperatively verify breast microcalcinates - N. V. Ponedelnikova; G. P. Korzhenkova; V. P. Letyagin; A. V. Petrovsky; Ya. V. Vishnevskaya; E. Yu. Kuzmicheva (Опухоли женской репродуктивной системы)
Information on the morphological type of a tumor is of crucial importance for successfully planning the treatment of patients with breast cancer (BC). Technological progress in the past decade has led to quality improvement in the diagnosis of particularly nonpalpable BC, one of whose manifestations is microcalcinates. Adequate use of mini-invasive procedures for obtaining materials for morphological analysis is favorable for extending the capabilities of accurate preoperative diagnosis verification to effectively plan a patient treatment and rehabilitation program.